MHD natural convection flow past an impulsively started infinite vertical porous plate with Newtonian heating in the presence of radiation - Narahari, M. (Emerald Group Publishing Ltd., 2016)
Purpose - The purpose of this paper is to investigate the effects of thermal radiation and viscous dissipation on steady natural convection flow of a viscous incompressible fluid along a uniformly moving infinite vertical porous plate with Newtonian heating in the presence of transverse magnetic field. The governing non-linear boundary layer equations are solved by using homotopy analysis method (HAM). The effects of various system parameters on velocity and temperature fields are discussed graphically, and the numerical values for skin friction and Nusselt number are presented in tabular form. Design/methodology/approach - The problem is formulated using the Boussinesq approximation under the effects of thermal radiation and transverse magnetic field. The resulting coupled system of non-linear differential equations is solved using HAM with appropriate boundary conditions for Newtonian heating of the plate. HAM is a powerful method which provides rapidly converging series solution for the velocity and temperature fields. The effects of Prandtl number, Grashof number, suction parameter, magnetic field parameter, radiation parameter and Eckert number on the fluid velocity, temperature, skin friction and Nusselt number have been investigated. Findings - The HAM solution has been successfully applied to find the converging series solution for velocity and temperature fields in terms of pertinent system parameters. Comparison of the exact solution results agree well with the HAM solution results in the absence of Eckert number and this indicates that the HAM solutions are accurate. It is found that the velocity and temperature profiles decreases with the increase of thermal radiation and suction parameters. An increase in the magnetic field parameter leads to a rise in the fluid temperature and fall in the fluid velocity. Research limitations/implications - The present analysis is limited to steady state laminar natural convection flow only. Unsteady natural- /mixed-convection laminar flow in the presence of thermal radiation, chemical reaction and transverse magnetic field will be investigated in a future work. Practical implications - The study provides very useful information for heat transfer engineers to understand the heat transfer rate when the moving vertical porous surface temperature is not known a prior. The present results have immediate relevance in the design of nuclear reactors where vertical moving porous plates are using as control rods. Originality/value - The present research work is relatively original and illustrates the effects of thermal radiation, viscous dissipation and transverse magnetic field on natural convection flow past a uniformly moving infinite vertical porous plate with Newtonian heating. Â© 2016 Emerald Group Publishing Limited.